Charakterystyka geochemiczna materii organicznej mezozoiku centralnej części Gór Krymskich - Zakrzewski, Adam (My University, 2014)
In this dissertation geochemical characteristic of organic matter in the Mesozoic strata of central part of the Crimean Mountains from Aj-Petri and Jalta massifs was performed. The analysed sediments in most cases contains minimal quantity of organic carbon, usually below 0.2 wt.% and traces quantities of hydrocarbons. Rocks from all examine samples have weak hydrocarbon potential. Geochemical researches shows predominance II type of kerogen with admixture of kerogen type III. The thermal maturity changes within the interval from 0,6 to 1,7 in Ro scale or “oil window” and “gas window” range. The thermal modeling reveled, that received the “oil window” phase of the Upper Jurassic organic matter in the Aj-Petri and Jalta massifs took place in the Paleocene and increase in this phase of maturity lasted until the middle Eocene.

W pracy dokonano geochemicznej charakterystyki materii organicznej utworów triasu i jury centralnej części Gór Krymskich z masywów Aj-Petri i Jałty. Analizowane utwory zawierają niewielkie ilości węgla organicznego, zwykle poniżej 0,2 % wag. oraz śladowe ilości węglowodorów. We wszystkich badanych próbkach stwierdzono słaby potencjał węglowodorowy. Badania geochemiczne wykazały obecność II typ kerogenu, z możliwymi domieszkami typu III. Dojrzałość termiczną materii organicznej oszacowano w przedziale dojrzałościowym od 0,6 do 1,7 w skali Ro, czyli w przedziale „okna ropnego” i „okna gazowego”. Modelowania procesów przyrostu dojrzałości materii organicznej wykazały, że utwory jury górnej masywów Aj-Petri i Jałty uzyskały fazę „okna ropnego” w przedziale czasowym paleogenu, a przyrost dojrzałości w tej fazie trwał do środkowego eocenu.
Geochemical characteristic of organic matter in the Mesozoic strata of the central part of Crimean Mountains
Keywords: Góry Krymskie; mezozoik; geochemia organiczna; dojrzałość termiczna; modelowania numeryczne; procesy generowania; Crimean Mountains; Mesozoic; organic geochemistry; thermal maturity; nemerical modeling; generation procesess